Future of SAW/BAW Devices in Mobile Radio - Maurer, Linus; Ruppel, Clemens; Weigel, Robert; Vazny, Rastislav (International Symposium on Acoustic Wave Devices, 2012)
The popularity of smart-phones has established EDGE/WCDMA/HSPA connectivity as de-facto minimum requirement with respect to cellular standards. This in turn has increased the pressure to lower costs on the Radio-Frequency Front-End (RFFE)setup.To reduce the complexity and to minimize costs and PCB area, the removal of the external inter-stage SAW and/or BAW filters in the receiver (Rx) and transmitter (Tx) front-end (FE) has become a mandatory feature of state-of-the-art full-duplex capable cellular radios in recent years[1].Furthermore, external SAW/BAW filters are an obstacle on the path to a fully configurable RFFE.This article gives a brief overview on recent developments with respect to the distribution of SAW/BAW filters in the RFFE and tries to elucidate the impact of LTE on the future RFFE partitioning.
elib2cris::1512001600,maurer2012